الأحوال الاجتماعية في مدينة أصفهان من خلال كتب البلدانيين - العليلى، حيدر مجيد حسين (جامعة الكوفة - كلية الآداب, 2015)
حفلت مدينة أصفهان بمكانة مهمة في التاريخ العالمي، كونها احدى اهم المراكز الحضارية في المشرق الاسلامي؛ ولاسيما بعد ان وطأها الفاتحون المسلمون عام 21ه/ 641 مـ، ومن ثم غدت مركزا لجذب القبائل العربية لتكون قبلة للرحالة والبلدانيين المسلمين الذين افاضوا في الكتابة عن احوالها السياسية والاجتماعية والاقتصادية، وليس من شك ان هذا النوع من المصنفات يعد من اوثق المصادر، لما تنطوي عليه من شهادات حية ومعاصرة عبر العصور الاسلامية؛ ونحن هنا لسنا بصدد الحديث عن مصنفات البلدانيين والجغرافيين المسلمين، بقدر سعينا الى تتبع احوال المدينة من النواحي الاجتماعية والاقتصادية والمبثوثة بين صفحات هذه المصنفات، لذا ارتأى الباحث الى تقسيم الدراسة الى وفقا لطبيعة المشاهدات الجغرافية ذات الصلة بالصبغة الاجتماعية لأصفهان من خلال استعراض التسمية ،والاصل، والمكون الاجتماعي، والحالة الاقتصادية ،والمراسيم والمناسبات الاجتماعية الواردة في المؤلفات البلدانية خلال العصور الاسلامية وقد خلصت الدراسة الى جملة من النتائج التي تبين وجود اهمية خاصة لمدينة اصفهان بالمقارنة مع البلدان الشرقية
Tile of research is the social circumstances in Isfahan city throughout the book of Muslims boldanees as acity of Isfahan considered one of major places in global history, as it is one of the most important cultural centers in the Muslim Orient; especially after the income Muslims in 21 AH / 641 AD, and then became the center of attraction of Arab tribes and Muslim traveler who wrote a lot about the political, social and economic conditions , there is no doubt that this kind of works is one of the sources that contains life certificates through the ages;Through this research it emerged that the Muslim geographers have attained a great and sophisticated in the curriculum of the historical and geographical blogging compared with stage medieval (third century AH-nineteenth century) in which these books have emergethe native of accurate details about Isfahan, topographiclly and statistically; as we see the touch of exaggeration to describe the city's climate and nature by muslims , although religious and sectarian diversity in Isfahan climatic was big factor on the natures of its people and their physical appearance human, and intellectual diversity of professions, seems that the ethnic and religious diversity had the effect of making the city's intellectual and cultural religious, which gave privacy from the rest of the cities of the provinces of the Orient ,Isfahan site locate on ways to road convoys helped in the growth of social evaluation that the source of a good entry and the prevalence of a state of relative economic stability throughout the seven Islamic calendar centuries despite contained on sectarian crises in the city signals.
Keywords: الاحوال الاجتماعية -- التاريخ -- كتب البلدان -- مدينة أصفهان